PENGARUH MEKANISME CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Arif Gigih Pramuharyo, 10.05.52.0042; Kartika, Andi (Students Journal of Accounting and Banking, 2015)
This study aims to transform and analyze the influence of the size of the board of directors, board of commissioner size, debt to equity and the size of the company to company performance in the manufacturing sector companies listed on the Indonesia Stock Exchange. In this study, researchers used a population yag manufacturing companies listed on the Stock Exchange during 2011-2013. The method used is purposive sampling method. Test equipment in this study using multiple linear regression, partial test (t test) and a simultaneous test of f (f test). The results of this study are the size of the board of directors of a significant positive effect on the performance of the company, board of commissioner size is not a significant negative impact corporate performance, debt to equity significant negative effect on the performance of the company and the size of the company significant negative effect on the performance of the company.Keywords: Board of Directors Size, Board of Commissioner Size, Debt To Equity, Firm Size and Firm Performance